Psychological disorders and help seeking behaviour among Malaysian medical students in their clinical years. - Aida J; Hizlinda T; Siti Fatimah S; Mohd Muhaimin A; Chai, SY; Sahrina W; Teo, BH (Penerbit UKM, 2014)
The present study is to determine the level of depression, anxiety and stress among Universiti Kebangsaan Malaysia (UKM) clinical year medical students and their help seeking behaviour in relation to their psychological aspect. A cross-sectional study was conducted in UKM Medical Centre for three months duration. The study population was the third, fourth and fifth year medical students via proportional sampling. They were given questionnaires consisting of socio-demographic items, Depression, Anxiety and Stress Scale 21 – Bahasa Malaysia version BM-DASS21 and questions regarding help-seeking behaviors. Psychometric assessment (BM-DASS21) estimated the level of depression, anxiety and stress among medical students. Help-seeking behavior questions assessed the use of medical facilities and other help-seeking sources. Regarding questions on the barriers towards seeking help from the primary health-care, three parts were evaluated: structural barriers, barriers towards perceptions on mental-health disorder and barriers towards use of primary health-care services. There were 380 medical students who were involved in this research. It was found that some students experienced depression (1.3%), anxiety (2.4%) and stress (2.4%). Majority of them preferred to seek help from friends (283; 74.5%) followed by parents (275; 72.4%). There was a significant association between students who were anxious and help seeking behaviour from formal sources: counselor (p=0.001) and religious personnel (p=0.03). Hence, it is essential to increase their awareness on psychological disorders and more efficient screening programme should be used to recognize medical students with possible emotional disorders.